Obtaining nonspherical poly(alkylcyanoacrylate) nanoparticles by the stretching method applied with a marketed water-soluble film. Issue 8 (24th May 2017) - Palazzo, Claudio; Ponchel, Gilles; Vachon, Jean Jacques; Villebrun, Sarah; Agnely, Florence; Vauthier, Christine
ABSTRACT: This work was aimed to produce elongated nanoparticles of clinical interest by the stretching method. Polymer films prepared from material recovered from the dissolution of a marketed stretchable water-soluble film were loaded with 10% of poly(isobutylcyanoacrylate) nanoparticles. The films were elongated at 50°C to 230% of their initial lengths. The shape factor of the nanoparticles recovered after elongation was consistent with stretching conditions applied on the film. This work has demonstrated the feasibility of the preparation of nonspherical poly(isobutylcyanoacrylate) nanoparticles by the stretching method and described conditions to apply the method. GRAPHICAL ABSTRACT: